“Doing and Being ‘Right’: Exploring Consumption, Materialism, Culture and Happiness in India - Chaudhuri, H.; Roy, R.A.J.A.T.; Rabbanee, Fazlul (2015)
The consumer subjective well-being arena, little attention has been paid to understanding the impact of interaction of unique cultural values and normative influence on overall life satisfaction. Here we focus on India to study subjective well-being, materialism, social comparison and the impact of belief in the Karma doctrine. Prior research suggests that materialism heightens expectations and lowers happiness, although many commercial research results show Indians are in general, happy despite multiple problems that may exist in the country. Here we examine how belief in karma or consequently, a value based justification, most likely counteracts the tendency to heighten psychological tension that characterise a typical materialist consumption (Burroughs &Rindfleisch 2002).Results show consumers are happy and Karma doctrine mediates happiness while materialism fully mediates the relationships of social visibility and social comparison with life satisfaction. Implications of these findings are discussed.